Respon Siswa dan Guru terhadap Komponen Model KNoS-KGS dalam Pembelajaran Biologi di SMA PGRI 1 Banjarmasin pada Konsep Ekosistem - Rezky Nefianthi; Muslimin Ibrahim; Yuni Sri Rahayu (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
Education in Indonesia has experienced several stages of change, start from infrastructure and policies and the curriculum. Professional teachers are required to be able to follow the changes, especially in the management of learning. The learning process that teachers in SMA PGRI 1 Banjarmasin still theoretical and memorizing. During this time teachers teaching always use discourse method, so the impact on the activity and student motivation is low. This study aims to investigate the response of students and teachers to the model KNoS-KGS in learning Biology at SMA PGRI 1 Banjarmasin. The population in this research are the students of SMA PGRI 1 Banjarmasin, whereas the sample is XI class. 25 students are choosing by random sampling. The technique of collecting the data using questionnaires. The average percentage of positive responses of students to the components and learning activities is on average 96.80. teacher's response to component and learning activities is positive, teacher believes that Model  KNoS-KGS very helpful (90.63%), assist (9.37), very good (96.88%), good (3.12). The results of data analysis can be concluded that the response of the students and teacher responses to the components of the model KNoS-KGS is positive.Keywords:        Students Response, Teacher Response, KNoS-KGS Model